Arthur Cooper. The Deep Woods' Business; uncollected translations from the Chinese by Arthur R. V. Cooper. Londres: Wellsweep Press, 1990. 96 pp. - Maeth Ch., Russell (Estudios de Asia y África, 1993)
-